VD_FINDINFO Jug / 2010 / 49 vom 9. Juni 2010 - VD Tribunal cantonal (2010)
PRÉVOYANCE PROFESSIONNELLE SELON LA LPP, RENTE D'INVALIDITÉ, RETRAITVOIE DE DROIT | 121 CPC, 160 CPC, 161 CPC, 73 LPP, 106 LPA-VD, 109 al. 1 LPA-VD, 109 al. 2 LPA-VD, 109 LPA-VD, 2 LPA-VD, 93 al. 1 let. c LPA-VD, 94 al. 1 let. c LPA-VD